No Irrelevant Jesus : On Jesus and the Church Today - Lohfink, Gerhard, 1934- (Book collections on Project MUSE., 2014)
Is Jesus relevant for today? If you think not, don't bother with this book. But if you think that Jesus might have something to say to today's world, which Jesus comes to mind? Is he "gentle Jesus, meek and mild," offering individual salvation but with no message for a suffering world? Is he to be remembered as a Zealot fighting for a hopeless cause or as an outstanding rabbi? Was he a prophet in the long series of Israel's prophets or a religious founder like Muhammad or Gautama? Or was Jesus unique, a man utterly consumed by zeal for the reign of God, by the "fierce urgency of now," the leader of a movement dedicated to God's cause but committed to nonviolence and living for others? If we seek him, can we find him in the churches? In No Irrelevant Jesus, Gerhard Lohfink, author of the acclaimed Jesus of Nazareth, explores these questions and offers a resounding yes to the relevance of Jesus today.